Determination of Caffeine in Coffee by Means Fourier Transform Infrared Spectrometry - Gallignani, Máximo; Torres, Marifred; Ayala, Carlos; Brunetto, María del Rosario (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this work a flow analysis-Fourier transform infrared spectrometric (FA-FTIR) method for the determination of caffeine in coffee was developed. The method involves the extraction, in batch, of caffeine from solid samples of roasted coffee with hot water (80°C), on-line retro-extraction of caffeine in chloroform and direct analysis of the organic phase by FTIR spectrometry. The measurement criterion selected for the quantification of caffeine was the absolute peak-valley value (1668-1649 cm”“1) of the first order derivate of the absorption spectrum, corresponding to the 1659 cm”“1 band. The method provides a limit of detection (3[1]) of 0.001% (w/v) caffeine, a relative standard deviation corresponding to the whole procedure, until the sample preparation, of 1.2% ([Caffeine] â‰ˆ0.05% (w/v), n = 5) andasample throughput (triplicate) of approximately 12 samples h”“1. The method was validated by means of standard addition, recovery and inter-day precision studies and by comparative analysis of real samples with the official chromatographic-spectrophotometric procedure. The method was applied to the analysis of commercial samples, obtaining a caffeine content ranging from 0.60 to 1.16% (w/w).